Prevalence and associated risk factors of temporomandibular disorders (TMD) in the Northern Finland Birth Cohort (NFBC) 1966 - Jussila, P. (Päivi) (Oulun yliopisto, 2019)
Abstract Temporomandibular disorders (TMD) are described as a variety of dysfunctions and pains related to the masticatory system. Clicking in the temporomandibular joints (TMJs) and pain in the masticatory muscles are the most common symptoms and signs of TMD. Other frequently reported symptoms are headache, facial pain, and symptoms in the ears. The prevalence of TMD signs in the adult population has been shown to vary between 33% and 86%, being more common in women than in men. TMD has been found to be most prevalent at 20–50 years of age. The aim of this cross-sectional study was to investigate the prevalence of TMD and associated risk factors in the Finnish adult population based on the Northern Finland Birth Cohort (NFBC) 1966. Altogether 1 962 cohort subjects at the age of 46 years (1 050 women, 912 men) responded to questionnaires and participated in a clinical medical and dental examination in 2012–2013. The stomatognathic examination was performed according to a modified protocol of diagnostic criteria for TMD (DC/TMD). The prevalence of TMD signs among the examined cohort subjects was 34.2%; women had clinical signs of TMD more often than men. Clinical signs were registered more often than self-reported TMD symptoms. The most common clinical signs were clicking in the TMJs (26.2%) and palpation pain in the masticatory muscles (11.2%). The most common diagnosis was disc displacement with reduction (7.0%). TMD signs were associated with unstable occlusion. Occlusal disturbances were associated with palpation pain in the masticatory muscles, as well as myalgia and arthralgia diagnoses. Pain-related TMD symptoms and clinical signs correlated strongly with a poor self-reported health condition as well as with painful general health problems. Tiivistelmä Purentaelimistön toimintahäiriöt (engl. temporomandibular disorders, TMD) on yhteisnimitys leukanivelten, puremalihasten, hampaiston ja niihin liittyvien kudosten sairaus- ja kiputiloille. Leukanivelen naksuminen ja kipu purentaelimistön alueella ovat ...